Comparison of Real-Time Methods Demonstrating the Effects of Reduced Glutathione on Olfactory Neuroblasts - Alain Géloën; Emmanuelle Berger (Applied Sciences)
The objective of the present study was to compare recent methods for characterizing cell modifications. We studied the effect of extracellular reduced glutathione (GSH) on an olfactory neuroblast cell line (13s24). Three methods were used to monitor, in label-free, noninvasive real-time experiments, cell surface occupancy by measuring impedance (xCELLigence), cell behavior (HoloMonitor cytometry), cell ultrastructure by measuring refractive index (3D Nanolive microscopy). Reduced glutathione dose-dependently increased cell volume and motility and decreased cell adhesion. Cell sorting analyses revealed that after short-term exposure (6 h), GSH reduced F-actin polymerization and extracellular glycoproteins leading to adhesion strength loss. Results support the hypothesis that excreted GSH could modulate disulfide bound-dependent integrin conformations involved in neurogenesis and/or neuronal plasticity. This is the first evidence of a causal link between GSH and changes in cell volume and motility required for cell division, migration, and/or differentiation. Results show the importance of real-time analysis methods, without labelling, in the study of cell responses under culture conditions. The present findings highlight important criteria in the choice of methods, beyond the parameters studied, such as cell preparation time, plate filling time, number of cells studied, friendly use of the devices, and the complexity of data processing.